2009
DOI: 10.1159/000200792
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Renal Function due to Warm Ischemia after Laparoscopic Partial Nephrectomy: Evaluation Using <sup>99m</sup>Tc-DMSA Renal Scintigraphy

Abstract: Introduction: The purpose of this study is, using technetium-99m-dimercaptosuccinic acid (99mTc-DMSA), to evaluate the decrease of renal function caused by warm ischemia. Patients and Methods: The 99mTc-DMSA scan was performed before and 1, 3 and 6 months after the operation for 19 consecutive patients. The patients were divided into three groups by warm ischemic time (group A: ≤40 min, B: >40 min ∩ ≤60 min, C: >60 min). Renal function of the unresected part was defined as the uptake to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…Our data are in concordance with a recent study by Tachikake et al, which concluded that increased intraoperative ischemic time during partial nephrectomy leads to kidney damage detectable by 99m Tc-DMSA renal scintigraphy. 14 …”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data are in concordance with a recent study by Tachikake et al, which concluded that increased intraoperative ischemic time during partial nephrectomy leads to kidney damage detectable by 99m Tc-DMSA renal scintigraphy. 14 …”
Section: Commentmentioning
confidence: 99%
“…10 The utility of nuclear scans for predicting postoperative renal insufficiency of the affected kidney after radical and partial nephrectomy has previously been demonstrated. 11-14 Nuclear scans can indicate damage to the affected kidney that is not reflected in serum creatinine measurements and eGFR calculations. 14 We believe long ischemia time and large tumor size predict for renal damage that will impact postoperative kidney function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, contralateral compensatory hypertrophy after partial nephrectomy can minimize postoperative GFR decrease in the two‐kidney model . As serum creatinine measurements and eGFR calculation cannot reflect the decreased renal function of the operated kidney, traditionally nuclear renal scan has been used to evaluate postoperative renal function . Among various types of nuclear renal scans, the 99m Tc‐DMSA renal scan is accepted as the most reliable method for quantifying cortical function and measuring the SRF .…”
Section: Introductionmentioning
confidence: 99%
“…6 As serum creatinine measurements and eGFR calculation cannot reflect the decreased renal function of the operated kidney, traditionally nuclear renal scan has been used to evaluate postoperative renal function. [7][8][9][10] Among various types of nuclear renal scans, the 99m Tc-DMSA renal scan is accepted as the most reliable method for quantifying cortical function and measuring the SRF. 11,12 In addition, as 99m Tc-DMSA cannot bind to renal tumor tissue, it is also used to visualize or distinguish the renal tumor from normal renal parenchyma.…”
Section: Introductionmentioning
confidence: 99%